Beyond Gender Stereotypes in Language Comprehension: Self Sex-Role Descriptions Affect the Brain’s Potentials Associated with Agreement Processing - Canal, Paolo; Garnham, Alan; Oakhill, Jane (Frontiers in Psychology, 2015)
We recorded Event-Related Potentials to investigate differences in the use of gender information during the processing of reflexive pronouns. Pronouns either matched the gender provided by role nouns (such as “king” or “engineer”) or did not. We compared two types of gender information, definitional information, which is semantic in nature (a mother is female), or stereotypical (a nurse is likely to be female). When they followed definitional role-nouns, gender-mismatching pronouns elicited a P600 effect reflecting a failure in the agreement process. When instead the gender violation occurred after stereotypical role-nouns the ERP response was biphasic, being positive in parietal electrodes and negative in anterior left electrodes. The use of a correlational approach showed that those participants with more “feminine” or “expressive” self sex-role descriptions showed a P600 response for stereotype violations, suggesting that they experienced the mismatch as an agreement violation; whereas less “expressive” participants showed an Nref effect, indicating more effort spent in linking the pronouns with the possible, although less likely, counter-stereotypical referent.